A Comparative Analysis of Competitive Intelligence Practices among Leading Cosmetic Brands - Ziaei Nafchi, Marjan (2024)
One of the world’s largest industries is the cosmetic industry with millions of customers all around the globe. The industry is so vast that it includes all sorts of items from personal care and beauty products. The cosmetic industry is growing rapidly as the demand for such products never seems to vanish. Statistics show that the revenue of the cosmetic market worldwide is currently around 108 billion dollars and it will reach up to approximately 129 billion dollars in 2028 (Statista, 2024). With that being said, in such a huge market, the competition can be challenging, and it is necessary that any company who wants to survive in this growing industry would utilize a strategic approach to stay ahead. The use of Competitive Intelligence (CI) practices has been a necessity leveraged by industry players over the years to maintain their position in the dynamic nature of the industry. Such practices include effectively gathering, analyzing, and leveraging information about market trends, consumer behavior, and competitor strategies. All of which are crucial for making informed and data-driven decisions, developing innovative products, and maintaining a competitive edge in the ever-evolving cosmetic industry. The aim of this thesis is to shed light on CI practices used by three leading cosmetic companies namely L’Oreal, Beiersdorf, and Estée Lauder, while observing their business strategies and their alignment with the practices.